The impact of cattle farming best management practices on surface water nutrient concentrations, faecal bacteria and algal dominance in the Lake Oconee watershed. (3rd September 2012) - Burt, Christopher; Bachoon, Dave S.; Manoylov, Kalina; Smith, Marka
Abstract The objective of this study was to assess water quality in the Lake Oconee watershed and evaluate the best management practices used by cattle farms to reduce water contamination. Inorganic nutrient concentrations, algal abundance and faecal bacteria were highest in the cattle farming areas. The diatom community where cattle had no access was dominated by Achnanthidium minutissimum (Kützing) Czarnecki and Fragilaria crotonensis Kitton, and in sites where cattle were allowed direct access to the lake, Asterionella formosa Hassal, Nitzschia palea (Kützing) Smith and Navicula rostellata Kützing dominated. The latter three taxa are well‐known high‐nutrient diatoms. High populations of green algae (coccoid Desmidiaceae) were found where cattle had access. Sources of faecal pollution were identified using polymerase chain reaction detection, with Bifidobacterium adolescentis as a marker of human faecal pollution and Bacteroides (BoBac) indicating cattle faecal pollution. Overall, riparian buffers were most effective at reducing pollution from cattle operations.